The Inverted yield curve and hidden Markov models in predicting future bear markets - Rihko, Olli (My University, 2020)
Previous studies have shown very clearly that there is a connection between the inversion of the yield curve and future recessions measured as contractions in the GDP. The focus of this study was, however, the connection between financial markets and the inverted yield curve, which has not been studied as much as the production related dependencies. Although it is difficult to draw a clear line between stock market crashes and the preceding inversions of the yield curve, the data suggests that the inverted yield curve is a sign of more volatile times ahead, which clearly heightens the risk of a major stock market down-turn. The empirical part of the study combined other factors and tools – hidden Markov models, credit spreads, S&P 500 returns, NY Fed recession probability model and the CAPE ratio – with the inverted yield curve in order to improve the predictability of future stock market crashes, which was then used to construct allocation strategies between the stock market and risk-free US Treasury rates. The proposed strategies managed to beat the benchmark and the conducted transaction cost sensitivity analysis proves that the strategies are feasible at reasonable transaction cost levels. The greater annualized returns and lesser volatility of the strategies lead to significantly better risk-adjusted returns than what one would achieve using the simple buy and hold strategy. The obtained Sharpe ratios range from 0,531 to 0,824, whereas the Sharpe ratio of the benchmark total US stock market return is 0,499 during the (pseudo) out-of-sample forecasting period of 1986–2019. It should be noted that the analysis is conducted using past data and the true acid test of the strategies will be made during the current inversion period. Although greater volatility leads to greater opportunities in the market, the effectiveness of the proposed strategies in this study is based on prudence and patience: the best option for the average investor could very well be to weather the storm in safer assets and then return to the stock market once the volatility of the market is lower again.

Aiempi tutkimus osoittaa selkeästi yhteyden kääntyneen korkokäyrän ja sitä seuraavan bruttokansantuotteen laskulla mitatun reaalitalouden laman välillä, mutta kyseisen korkokäyrän vaikutuksia rahoitus- ja ennen kaikkea osakemarkkinoilla ei ole akateemisesti tutkittu yhtä paljon kuin kansantaloustieteellisiä vaikutuksia. Vaikka selkeitä syy-seuraussuhteita osakemarkkinaromahdusten ja niitä edeltävien korkokäyrien kääntymisten välille on vaikea vetää, läpikäyty aineisto osoittaa kääntyvän korkokäyrän olevan merkki lähitulevaisuudessa kasvavasta volatiliteetista, joka kasvattaa olennaisesti vakavan osakemarkkinaromahduksen riskiä. Tutkimuksen empiirinen osuus yhdistää kääntyvään korkokäyrään muita faktoreita ja työkaluja – kuten esimerkiksi piilotetut Markov-mallit, korkospreadit ja S&P 500 -tuotot –, joiden avulla pelkän korkokäyrän ennustevoimaa pyritään parantamaan sekä siten muodostamaan toimivia allokaatiostrategioita osakemarkkinoiden sekä riskittömän tuoton välillä. Esitetyt strategiat onnistuivat voittamaan vertailuindeksinsä ja transaktiokustannuksista tehty herkkyysanalyysi osoittaa, että muodostetut strategiat ovat toteuttamiskelpoisia realistisilla transaktiokustannuksilla. Strategioiden vertailuindeksiä parempien keski-määräisten vuosituottojen sekä pienemmän volatiliteetin ansiosta niiden riskikorjattu tuotto on merkittävästi parempi kuin pelkästään vertailuindeksiin sijoittamalla. Tutki-muksessa esitettyjen strategioiden Sharpen luvut ovat välillä 0,531–0,824, kun taas vertailuindeksinä toimivan koko Yhdysvaltain osakemarkkinan kokonaistuoton Sharpen luku on 0,499 aikavälillä 1986–2019, joka toimii tutkimuksen (pseudo-)ennustejaksona. On kuitenkin huomattava, että strategioiden todellinen tulikoe tapahtuu vuonna 2019 tapahtuneen korkokäyrän kääntymisen jälkeisessä lähitulevaisuudessa. Vaikka suurempi volatiliteetti johtaa suurempiin mahdollisuuksiin markkinoilla, niin tässä tutkimuksessa esitettyjen strategioiden tehokkuus perustuu ennen kaikkea kärsivällisyyteen ja varovaisuuteen: tavallisen sijoittajan paras vaihtoehto markkinoiden mylleryksessä voisi useimmiten olla hakeutuminen turvallisempien omaisuuserien pariin sekä palaaminen osakemarkkinoille myrskyn laantuessa.
Keywords: inverted yield curve, hidden Markov models, credit spreads, allocation strategies